2021
DOI: 10.3390/ijms221910549
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 and Free Indoxyl Sulfate Levels Are Associated with miR-126 in Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a major cause of death worldwide and is associated with a high risk for cardiovascular and all-cause mortality. In CKD, endothelial dysfunction occurs and uremic toxins accumulate in the blood. miR-126 is a regulator of endothelial dysfunction and its blood level is decreased in CKD patients. In order to obtain a better understanding of the physiopathology of the disease, we correlated the levels of miR-126 with several markers of endothelial dysfunction, as well as the represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…A meta-analysis comprising data from 11 studies revealed that indoxyl sulfate and p-cresyl sulfate were found to be independently linked to an increased risk of cardiovascular events and mortality in patients with CKD [72]. Another study suggests that only indoxyl sulfate, and not p-cresyl sulfate signaling, can be linked to altered miR-126 expression, which has been implicated in vascular endothelial functions, angiogenesis, and consequently the pathogenesis of CKD [73].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis comprising data from 11 studies revealed that indoxyl sulfate and p-cresyl sulfate were found to be independently linked to an increased risk of cardiovascular events and mortality in patients with CKD [72]. Another study suggests that only indoxyl sulfate, and not p-cresyl sulfate signaling, can be linked to altered miR-126 expression, which has been implicated in vascular endothelial functions, angiogenesis, and consequently the pathogenesis of CKD [73].…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative polymerase chain reaction (qPCR) reactions were performed on a 7900HT Standard Real‐Time PCR System (Applied Biosystems Inc.) thorough the miScript SYBR Green PCR Kit (Qiagen). miR‐144‐5p expression was estimated using the 2 −ΔΔ C t method [14]. RNA was extracted from rat serum and kidney tissue for RT‐qPCR.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of several uremic toxins on vascular dysfunction may also be due to their ability to modulate the downstream expression of many intracellular miRNAs in endothelial cells [ 73 , 74 ]. Altogether, this evidence highlights that uremic toxins may represent the missing player between endothelial damage and uremia-related CVI.…”
Section: The Gut–kidney Axismentioning
confidence: 99%